RESEARCH ON COMPRESSIVE PERFORMANCE OF 304 STAINLESS STEEL MULTI-LAYER GRADIENT LATTICE AND GRADIENT RATE INFLUENCE - XU XiangCong; GAO JiaLi; HAO YunBo2 (Jixie qiangdu)
In this paper, the energy absorption performance of the variable density multilayer gradient lattice metal vibration damping structure was studied by experimental and finite element analysis. Firstly, two kinds of gradient lattice structures of variable diameter BCC (DBCC) and variable angle BCC ( ABCC) were designed based on the body-centered cubic ( BCC ) structure, and the multi-layer gradient structures of 304 stainless steel were prepared by selective laser melting process. Then, the compression and energy absorption properties of the gradient lattice structure and the uniform lattice structure were comparatively studied. Both the finite element simulation and the experimental results indicated that for the DBCC structure, the low-density layer drived the high-density layer to collapse layer by layer since the compression was started. A high energy absorption efficiency was obtained in the small strain stage. However, stress distribution was uneven, resulting in a significant decrease in its mechanical properties and overall energy absorption rate compared with the uniform structure. The ABCC structure performed a strong compressive performance in the stage of small strain, and was collapsed layer by layer in the large compression strain stage, thus improved the energy absorption performance to a certain extent. In addition, increasing the gradient rate of the structure effectively improved the elastic modulus and energy absorption characteristics of the ABCC structure.